MOTIVASI MASYARAKAT DALAM MEMELIHARA DAN MEMPERTAHANKAN GIGI - Lendrawati Lendrawati (Andalas Dental Journal, 2013)
Motivation is a fundamental impulse that drives a person to behave in undertaking activities that are expected. Motivation as a concept that is used when the self emerged a desire and drive or direct behavior. The higher the intensity the higher the motivation of behavior. Maintaining a fixed gear means an action to prevent tooth decay, dental care for the sick and restoring damaged teeth and abnormalities of the hard and soft tissues to restore tooth form and function, aesthetic value and protection of the supporting tissues of the teeth and maintaining teeth as long as possible in the oral cavity. Knowledge of dental disease is important to know how to maintain healthy teeth to increase the motivation to maintain one's teeth Knowledge gained will form the attitude is a predisposition for sustaining behavior teeth.